Curvas de Bézier - Almeida, Evert Elvis Batista de (2015)
In this work we will make an introduction an important application mathematics called Bézier curves. The history of this curve originated in industry automobile French , and found many applications in various elds of science. Revisit some concepts such as parametric functions, polynomials Bernstein and interpolation for de nition the curves Bézier. We will discuss the algorithm Casteljau which facilitates the construction of the curve and determine derivative. Throughout the text we will implement some examples with Geogebra software and LATEX in addition to discuss relevant issues that arouse public interest.